Intestinal parasites and hookworm species in stray cats, dogs and soil: An epidemiological approach to study soil contamination with zoonotic parasites / Sandee Tun - Sandee , Tun (2016)
The study was conducted to determine the prevalence of intestinal helminth eggs and protozoa excreted in the faeces of stray cats and dogs as well as in soil samples. A total of 379 fresh faecal samples (from 227 dogs and 152 cats) and 126 soil samples were collected. The egg and (oo)cyst stages were detected via microscopy after the application of formalin–ether concentration technique. Genomic DNA was extracted from the samples containing hookworm eggs and used for further identification to the species level using real-time polymerase chain reaction coupled with high resolution melting analysis. Microscopic observation showed that the overall prevalence of helminth eggs among stray cats and dogs was 75.7% (95% CI = 71.2%–79.9%), of which 87.7% of dogs and 57.9% of cats were infected with at least one parasite genus. Five genera of helminth eggs were detected in the faecal samples, including hookworms (46.4%), Toxocara (11.1%), Trichuris (8.4%), Spirometra (7.39%) and Ascaris (2.37%). The prevalence of helminth infections among stray dogs was significantly higher than that among stray cats (p < 0.001). Only three genera of helminths were detected in soil samples with the prevalence of 23% (95% CI = 15.1%–31%), consisting of hookworms (16.6%), Ascaris (4%) and Toxocara (2.4%). The molecular identification of hookworm species revealed that Ancylostoma ceylanicum was dominant in both faecal and soil samples. The dog hookworm, A. caninum, was also detected among cats, which is the first such occurrence reported in Malaysia to date. This finding indicated that there was a cross-infection of A. caninum between stray cats and dogs because of their coexistence within human communities. As for protozoa (oo)cysts, the overall prevalence was 20.3%, with 22.4% in cats and 18.9% in dogs. Four genera of protozoa (oo)cysts were detected, including Giardia (8.2%), Isospora (3.4%), Cyclospora (4.2%) and Cryptosporidium (4.5%). Only two genera of protozoa were detected in soil samples with the prevalence of 9.5% in which Isospora (7.1%) iv being the commonest protozoan detected, followed by Giardia (2.4%). Taken together, these data suggest the potential role of stray cats and dogs as being the main sources of environmental contamination with zoonotic intestinal parasites which potentially involve in human infections.